Implication of the training ad continuing education process for the interprofessional performance - Carine Vendruscolo; Letícia de Lima Trindade; André Lucas Maffissoni; Jussara Gue Martini; Cláudio Claudino da Silva Filho; Juliana Vieira de Araujo Sandri
ABSTRACT Objetives: to analyze the implication of the training/continuing education process of professionals of the Expanded Nucleus of Family Health and Basic Care (Portuguese acronym: Nasf-AB) for their interprofessional performance. Methods: a qualitative case study performed with Nasf-AB teams representative of four macro-regions of health of the state of Santa Catarina. Participation of 43 professionals, who answered collective interviews. The results were later submitted to thematic analysis. Results: the training is strongly influenced by the Biomedical Model, which acts as an obstacle to interprofessional performance, given the challenges in the daily routine of Nasf-AB professionals. Continuing education emerges as a potential for the successful collaborative work among teams, and between the teams and Family Health professionals. Final considerations: there are important limits in the training of professionals. However, the constant interprofessional development promoted by strategies of continuing education contributes to broaden the support and collaborative practices that qualify services and strengthen Basic Care.